Particle Swarm Optimization based modelling of a surface ship using free running experimental approach. Issue 1 (February 2021) - Wang, Y; Chai, S; Nguyen, H D; Liu, J; Ma, F
Abstract: System modelling of the surface ship, which could be regarded as a multi-variable parameter estimation problem, has attracted tremendous interests from researchers since it is of key importance to development of ships' control system. The aim of this study is to utilize the Particle Swarm Optimization (PSO) algorithm to get the optimized solution of hydrodynamic coefficients in the presence of ship's mathematical model using the space search principle. The motion equations of the ship in four degrees of freedom are formulated to clarify the scheme of the model. After expressing the theory of the PSO method, the system identification of the ship's motions is conducted to estimate the hydrodynamic coefficients. By using the identified parameters, the mathematical motion model of the free-running ship, namely 'P and O Nedlloyd Hoorn', is developed. The comparison between the experiment measurements and simulation trails and attitudes have indicated that the developed mathematical is sufficient and effective to response the ship's motions. Therefore, it is demonstrated that the PSO based system identification algorithm is capable of conducting system identification and system modelling for the surface ship through free running approach.